Association between fetal exposure to the Chinese famine and cognitive decline in adulthood: a retrospective cohort study - Xiang, Shuai; Li, Yixuan; Dong, Bingzi; Chi, Haochen; Wang, Yangang; Liu, Shanglong (Frontiers in Nutrition, 2025)
BackgroundThe Great Chinese Famine in the 1960s represents a significant historical event with potential long-term health consequences. This study aims to investigate the impact of famine exposure during different developmental stages (fetal, preschool, school-age, and unexposed) on cognitive function in adulthood.MethodsA retrospective cohort study was conducted among 4,067 participants from the China Health and Retirement Longitudinal Study (CHARLS) database. Participants’ famine exposure histories were categorized based on birthdates and famine severity, and their cognitive function was assessed in adulthood. Multiple linear regression analysis was used to explore the relationships between famine exposure during different life stages and average cognitive score from 2011 to 2015.ResultsOur study showed that fetal exposure to famine was significantly associated with lower cognitive function scores in adulthood, compared to individuals who were not exposed or exposed during other life stages (preschool or school-age). After adjusting for confounding factors, the fetal exposed group showed a statistically significant decrease in global cognition (β = −0.60, 95% CI: −0.95, −0.25), episodic memory (β = −0.25, [95% CI: −0.42, −0.07]), and executive function (β = −0.36, [95% CI: −0.61, −0.10]) compared to the non-exposed group. Furthermore, participants from severely affected famine areas exhibited significantly lower cognitive function scores compared to those from less severely affected famine areas after adjusting for all confounding factors.ConclusionFetal exposure to severe famine was associated with reduced cognitive performance in adulthood. This study provided new evidence for developing prevention and treatment strategies for cognitive decline.